2008
DOI: 10.1055/s-2008-1067097
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity Control in 1,2- and 1,4-Additions of Aluminum Organyls to Carbonyl Compounds

Abstract: Aluminum organyls are valuable reagents for carboncarbon bond formation as they can either be purchased at low prices or conveniently be prepared, for example, by hydro-or carboalumination of alkenes and alkynes. Although their application in reactions with a,b-unsaturated carbonyl compounds is rather limited, it creates a diverse picture concerning the selectivity of product formation which depends on several factors such as the type of organic residue, the conformation of the enone, the presence of additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…α,β‐Unsaturated carbonyl compounds are important building blocks in organic synthesis and are commonly used as substrates in a wide variety of transformations including Michael additions,1 Diels–Alder reactions,2 cyclopropanations3 and a wide variety of organocatalytic processes 4. This diversity in application makes them common intermediates in the total synthesis of natural products and the synthesis of drug molecules.…”
Section: Introductionmentioning
confidence: 99%
“…α,β‐Unsaturated carbonyl compounds are important building blocks in organic synthesis and are commonly used as substrates in a wide variety of transformations including Michael additions,1 Diels–Alder reactions,2 cyclopropanations3 and a wide variety of organocatalytic processes 4. This diversity in application makes them common intermediates in the total synthesis of natural products and the synthesis of drug molecules.…”
Section: Introductionmentioning
confidence: 99%
“…As the main objective of these studies is reactions of β‐substituted cyclopentenones, we selected 6 a to serve as the representative substrate (Table 1). Our focus on aluminum‐based reagents10 is partly due to the higher reactivity as well as the significantly lower cost of this class of alkylating agents (vs. dialkyl zinc reagents).…”
Section: Methodsmentioning
confidence: 99%
“…The copper‐catalyzed 1,4‐addition of organometallic reagents to α,β‐unsaturated compounds is a powerful method for the efficient construction of carbon–carbon bonds 1. Highly reactive nucleophiles such as Grignard reagents,1ac, 2 diorganozinc compounds,1d,e, 3 and triorganoaluminum compounds1df, 4 are widely employed in these reactions, but the use of milder nucleophiles has been much less studied; in fact there has been only one such study reported, wherein Lee and Hoveyda used organo(trifluoro)silanes as nucleophiles in the presence of a fluoride additive 5. In contrast, although the use of organoboronic acids and their derivatives would be highly attractive in view of their availability, stability, and ease of handling, there has been no such report to date as far as we are aware 6–8.…”
Section: Copper‐catalyzed 14‐addition Of Phenylboronate 2 To Electromentioning
confidence: 99%